Stochastic model of oscillatory diffusion for colloidal particles in a fixed porous bed. (31st December 2021) - Curran, Kelly; Marshall, Jeffrey S.
Graphical abstract: Highlights: Oscillatory diffusion results from flow oscillation plus random particle hindering. Enhances nanoparticle transport in biofilm mitigation and targeted drug delivery. A stochastic model of oscillatory diffusion was investigated. Parametric sensitivity study was performed for various model parameters. Stochastic model predictions agreed with CTRW theory with restrictions. Abstract: Colloidal particles in the pore spaces within a packed bed move back and forth in response to an imposed oscillatory flow, such as that associated with an acoustic field. The diffusive motion of the particles results from intermittent hindering of the oscillatory motion, which we assume to result from particle filtration by the packed bed pore spaces. We consider an experimentally-validated stochastic model that entails a series of transitions between an oscillatory state, where the particle oscillates with the fluid flow, and a captured state, where the particle is held fixed in the bed. The paper examines sensitivity of this stochastic model to different parameters and compares the stochastic model predictions for diffusion coefficient with predictions of an analytical solution based on continuous-time random walk (CTRW) theory. The results are relevant to applications such as nanoparticle penetration into biofilms, drug capsule penetration into human tissue, and microplastic transport within saturated soil.